Entrepreneurship Challenges in Sport Colleges - Mondalizadeh, Zeinab (Journal of Entrepreneurship, Business and Economics; Vol 6 No 2 (2018), 2018)
The purpose of this study was to determine the challenges of entrepreneurship in sport colleges in Iran and presenting reformation policies. The study was a descriptive survey and used the research-designed questionnaire. The statistical sample was selected 64 subjects simple randomly across statistical populations (79) including professors and Ph.D. students of sport management in Tehran's universities. Data were analyzed by the Friedman test (χ 2 = 46.97, ρ≤.001). The result showed that the most important entrepreneurship challenges in sport colleges were status of sports entrepreneurial consulting services, present the programs of entrepreneurship training, the status of research and development unit, and innovation system in physical education colleges, the status of profitable from the research results and disproportion between educational contents and job skills. A survey of conflicts and challenges entrepreneurship in sport colleges emphasizes on long-term planning and attention for employing and using the safe planning by competence managers to provide background for entrepreneurship, innovation, and science production. Research paper Keywords: Challenges, Entrepreneurship, Physical Education Colleges, Sport, Education Reference to this paper should be made as follows: Mondalizadeh, Z. (2018). Entrepreneurship Challenges in Sport Colleges of Iran, Journal of Entrepreneurship, Business and Economics , 6 (2), 12–28.